COVID‐19 as an occupational disease. Issue 4 (24th January 2021) - Carlsten, Christopher; Gulati, Mridu; Hines, Stella; Rose, Cecile; Scott, Kenneth; Tarlo, Susan M.; Torén, Kjell; Sood, Akshay; de la Hoz, Rafael E.
Abstract: The impact of coronavirus disease 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus 2 permeates all aspects of society worldwide. Initial medical reports and media coverage have increased awareness of the risk imposed on healthcare workers in particular, during this pandemic. However, the health implications of COVID‐19 for the global workforce are multifaceted and complex, warranting careful reflection and consideration to mitigate the adverse effects on workers worldwide. Accordingly, our review offers a framework for considering this topic, highlighting key issues, with the aim to prompt and inform action, including research, to minimize the occupational hazards imposed by this ongoing challenge. We address respiratory disease as a primary concern, while recognizing the multisystem spectrum of COVID‐19‐related disease and how clinical aspects are interwoven with broader socioeconomic forces.